The Effects of Budget Transparency, Human Resource Quality, and Information Technology on Village Financial Management in All Villages of Batang Serangan District Langkat Regency - Khairani Agustin; Dito Aditia Darma Nasution; Miftha Rizkina (Utan Kayu Publishing, 2025)
This study aims to examine the influence of budget transparency, human resource quality, and information technology on village financial management in Batang Serangan District Langkat Regency. This study is a causal associative research using a quantitative approach. The sample in this study consisted of 62 village officials from 7 villages in Batang Serangan District. The data collection technique used a questionnaire measured with a Likert scale. This study used multiple linear regression analysis techniques with the help of IBM SPSS Statistics Version 31 software. The research results indicate that partially, budget transparency has a positive and significant effect on village financial management (significance value 0.0150.05). Human resource quality partially has a positive and significant effect on village financial management (significance value 0.009 0.05). Similarly, information technology partially has a positive and significant effect on village financial management (significance value 0.007 0.05) and becomes the most influential variable with an Adjusted R Square of 0.792 or 79.2%. Simultaneously, budget transparency, the quality of human resources, and information technology have a positive and significant effect on village financial management (significance value ,0010.05).